Economic Integration in South Asia: Opportunities and Challenges - Tanweer Shahid; Azhar Ahmad (National University of Modern Languages (NUML), Islamabad, 2021)
Regional economic integration stimulates cooperation to uplift socio-economic quality of a region. Although economic integration may, sometimes, result in lesser independence of states, the benefits often outweigh the limitations. Despite encouraging growth in South Asia (pre-Covid-19 period), its contribution in global GDP remains minimal. Trust deficit, reluctance of states, political and security issues, lack of sustaining infrastructure, are some factors affecting gainful integration. Regional economic integration, nevertheless, offers exciting prospects to synergise mutual comparative advantages, trade and commercial gains, investment opportunities in other states. This paper analysis various initiatives within the South Asian region and their impact on regional integration. The pandemic of Covid-19 has worsened socioeconomic predicament and trade transactions in the region. Given the socio-economic and poverty issues, SAARC integration can aid in political stability, socio-economic development thus ensuring overall growth of the region and individual countries.